Caracterização de genótipos de alface para baby leaf sob diferentes densidades de fluxo de fótons fotossinteticamente ativos em cultivo vertical indoor - Pimentel, Fernanda Abduche Galvão (Universidade Federal de São Carlos, 2024)
Indoor cultivation systems have gained prominence in recent years, where photosynthetically active photon flux density (PPFD) is one of the artificial lighting parameters that can influence plant development. Research with tropicalized lettuce cultivars is non-existent, making it necessary to improve baby leaf production using artificial lighting in order to find the ideal PPFD. The objective of the present work was to verify whether lettuce genotypes respond differently to PPFD, in order to find the best PPFD and the best genotypes. The experiments were conducted at the IAC indoor laboratory in Campinas SP. Four treatments were distributed in the cultivation racks, in randomized blocks, with PPFDs of 80, 110, 140 and 170 µmol m-2 s-1, respectively. In the first experiment, eleven genotypes and one commercial cultivar were used and in the second, with the same irradiances, three genotypes were used, selected from the first. In both cases, assessments of canopy height, number of leaves, fresh and dry matter mass, productivity and instrumental color were carried out. Only in the second, analysis was carried out on leaf area, total chlorophyll a and b content, carotenoids, moisture, ash, pH, total titratable acidity, total soluble solids and sensorial. In the first experiment, it was possible to observe an interaction between the genotypes and the PPFDs, referring to the observed characteristics. In the second experiment, there was no difference between lettuce genotypes for agronomic characteristics, however, for the PPFDs applied, 170 µmol m-2 s-1, guaranteed the highest plant productivity (3.54 kg m-²), higher levels of chlorophyll a (0.43 mg g-1) and greater preference among consumers. Therefore, genotypes 281-3-2-2 (curly), 293-6-1-1 (mimosa) and 204-1-1-1 (smooth) are recommended, conducted with a DFFF of 170 µmol m- 2 s-1 in an indoor cultivation system for the production of lettuce baby leaves, as they all presented the best values for the analyzed characteristics.
Characterization of lettuce genotypes for baby leaf under different photon flux densities photosyntetically assets in vertical indoor cultivation
Keywords: Lactuca sativa L.; DFFF; Iluminação artificial; Cultivo vertical indoor; Melhoramento genético; PPFD; Artificial lighting; Indoor vertical cultivation; Sustainability; Genetic improvement; CIENCIAS AGRARIAS::AGRONOMIA; CIENCIAS AGRARIAS